(untitled) - Wilson, Ken (New York, 2007)
Smart Choice is a complete four-skills course with a special focus on conversation. With its straightforward approach, the series requires minimal preparation, while allowing plenty of opportunity for supplementation. Each page of Smart Choice offers a self-contained lesson, focusing on a particular skill, and closes with a discussion activity. A balance of work on speaking, listening, reading, writing, grammar, vocabulary, and pronunciation ensures a high level of student engagement, as well as mutual reinforcement of the language skills.
Keywords: English language; textbooks for foreign speakers